Kendall's advanced theory of statistics volume 2A classical inference and the linear model - Stuart, Alan; Stuart, Alan, 1922-; Ord, J. K.; Arnold, Steven F., 1944-; O'Hagan, Anthony (London : Edward Arnold, 1999)
A book on advanced statistics. This Volume 2A is the completely updated Volume 2 - Classical Inference and Relationship.
v. 2A. Classical inference and the linear model / Alan Stuart, J. Keith Ord, Steven Arnold (6th ed., 1999)
Vol. 2A (1999) has imprint: London : Arnold ; New York : Oxford University Press.
Includes bibliographical references and indexes.
rua 03/03/15
Loans
Keywords: Mathematical statistics